LEARNING NATIONALISM: THE RELATIONSHIP AMONGST INTER-STATE WAR, THE NATIONALISATION OF THE HABSBURG EMPIRE, AND THE EMERGENCE OF THEODOR HERZL'S POLITICAL ZIONISM - Romany, Travis Justin (Trinity College Dublin. School of Religion. Discipline of School of Religion, 2026)
There is an established, theorised relationship in International Relations amongst inter-state war, the centralisation of modern states, and the emergence of political nationalism within them. This claim was famously encapsulated in Charles Tilly's 1975 aphorism "War made the state and the state made war." Theorists of nationalism, like Charles Tilly, argue that nationalism spread across the global inter-state system because nation-states were more successful in inter-state wars compared to non-nationalised states. This work goes beyond conventional theories of modern nationalism when it argues that inter-state war did not only incentivise the centralisation and nationalisation of states but it may have been responsible for the creation of national identities themselves. This work uses the emergence of Theodor Herzl's political Jewish nationalism, or Political Zionism, in the modern Austro-Hungarian state to test its claims. The first claim is that the political choices made during the modern centralisation of the Austro-Hungarian Monarchy resulted in a distribution of social power that was biased towards Catholic, Austro-German, men in Austria by Vienna's Liberal Era (1867-1879). The second hypothetical claim is that biased, centralised, state institutions in Austria, and its capital of Vienna, created observable patterns of durable inequality between groups by the 19th Century. These patterns of durable inequality were based on objective social relations but were later defined as subjective national identities by groups who perceived that their social success aligned with categories of durable inequality. Finally, this work argues that the dominant political nationalism in Vienna by the late 19th Century was led by Christian, Austro-German, men who formalised Vienna's patterns of durable inequality in its political system via the nationalist exclusion of competitive Jews. It concluded that Theodor Herzl responded to the insecurity of Jews in 19th Century Vienna by calling for a Jewish nation-state as a means of solving their social inequality. Theodor Herzl created and defined the Jewish national identity as a result of his exclusion from the Viennese political system.
APPROVED
Keywords: Zionism; Israel; Nationalism; Habsburg; Vienna; International Relations; Herzl; Jew